A 10‐Year Study of Dermatophytoses in Isfahan, Iran. Issue 2 (23rd April 2015) - Chadeganipour, Mostafa; Mohammadi, Rasoul; Shadzi, Shahla
Abstract : Dermatophyte infections are very common worldwide and their epidemiological characteristics vary according to the geographical region and have altered in the last decades. The aim of the present investigation was to determine the diversity of causative agents of dermatophytoses and describe the epidemiological condition of infection in Isfahan, Iran, between 2003 and 2012. Specimens were collected from hair, nail, and skin and were examined by conventional methods such as direct microscopy, culture on sabouraud dextrose agar with chloramphenicol and cycloheximide (Mycosel agar) and sabouraud glucose agar, Trichophyton agars, growth on rice grains, urease test, and hair perforation test. Of 13, 469 clinically suspected cases, 11.5% were affected with dermatophytoses. Tinea capitis was the most frequent form of infection (52.7%), followed by tinea corporis (24%), tinea pedis (8.9%). Trichophyton verrucosum was the most prevalent causative agent (40.6%), followed by T. mentagrophytes var. interdigitale (17.6%), Epidermophyton floccosum (13%), T. violaceum (12%), T. rubrum (4.1%). Age range of patients was between 1 and 80 years. Housewives were the most patients in our study. The study emphasizes importance of epidemiological surveys of dermatophyte species for the better management of infection.